Ideal and Resistive Magnetohydrodynamic Two-Dimensional Simulation of the Kelvin-Helmholtz Instability in the Context of Adaptive Multiresolution Analysis - GOMES,A.K.F. (2017)
ABSTRACT This work is concerned with the numerical simulation of the Kelvin-Helmholtz instability using an ideal and resistive two-dimensional magnetohydrodynamics model in the context of an adaptive multiresolution approach. The Kelvin-Helmholtz instabilities are caused by a velocity shear and normally expected in a layer between two fluids with different velocities. Due to its complexity, this kind of problem is a well-known test for numerical schemes and it is important for the verification of the developed code. The aim of this paper is to verify the implemented numerical model with the well-known astrophysics FLASH code.